Development of high-performance organic solvent-resistant thin-film composite membranes for small molecule separation via an enhanced interfacial polymerization strategy - Changling Yu; Ziye Wang; Biao Ma; Jiaxin Zhang; Zhenlong Wang; Honglin Huang; Song Cao; Guangyu Li; Chao Wu; Yuanzhen Li (Journal of Environmental Chemical Engineering, 2026)

Predicting heat-induced hazardous compounds in roasted almonds via browning index and moisture using machine learning - Yunhao Xia; Buyu Liu; Kaijun Wang; Zhongwu Yu; Wenhan Yan; Changling Wu; Guanyu Fang; Fenghua Wu; Xingquan Liu; Peng Wang (Food Chemistry, 2026)

Regulation of aerobic methane oxidation by methane concentration: insights from cultivation experiments - Qikun Tian; Yu Zhen; Jing Li; Xiaoqing Xu; Changling Liu (Acta Oceanologica Sinica, 2025)

Genomic analysis of modern maize inbred lines reveals diversity and selective breeding effects - Kaijian Fan; Mohsin Ali; Kunhui He; Yingwei Feng; Tingxi Yu; Hao Zhang; Tai An; Weiwei Zeng; Junjie Fu; Ying Zhou; Yanfang Heng; Fei Gu; et al. (Science China Life Sciences, 2025)

Fungal fermentation improves the nutritional quality, flavor characteristic and physicochemical property of highland barley bran - Yongzhu Zhang; Mingxin Liu; Fenghua Wu; Jinmei Li; Fidelis Azi; Ke Yu; Zhiping He; Peng Wang; Changling Wu; Baiyi Lu; Xingquan Liu (Journal of Cereal Science, 2024)

Optimized improvement of double-stage solar AES saline wastewater treatment system based on performance simulation and exergy analysis - Jing Yu; Yujiang Xia; Changling Wang; Juan Yang; Weidong Yan; Sumin Jin (Desalination, 2024)

Spatial distribution and environmental/biological co-regulation mechanism of dimethyl sulfur compounds in the eastern Indian Ocean - Liying Peng; Chenjuan Fan; Yu Guo; Changling Ding; Xingzhou Wang; Guicheng Zhang; Jun Sun (Frontiers in Marine Science, 2024)
Dimethyl sulfur compounds including dimethylsulfoniopropionate (DMSP), dimethyl sulfide (DMS), and dimethyl sulfoxide (DMSO), play a crucial part in global sulfur cycling. The eastern Indian Ocean (EIO), characterized by its remarkable diversity of biomes and climate dynamics, is integral to global climate regulation. However, the regulation mechanism of DMS (P, O) in the EIO remains to be elucidated in detail. This paper presented a field survey aimed at investigating the spatial distribution of DMS (P, O) and their relationships with environmental and biological factors in the EIO. The surface concentrations of DMS, DMSPt, and DMSOt varied from 0.07 to 7.37 nmol/L, 0.14 to 9.17 nmol/L, and 0.15 to 3.32 nmol/L, respectively, and their distributions are attributed to high Chl-a concentration near Sri Lanka and the influence of ocean currents (Wyrtki jets, Bay of Bengal runoff). Higher concentrations of DMS (P) and DMSOt were predominantly observed in water columns shallower than 75m and deeper than 75m deep, respectively. The monthly DMS fluxes in the study area peaked in August. Temperature and Dissolved Silica Index (DSI) were the key environmental determinants for DMS distribution, while nitrate (NO 3 - ) was the primary factor for both DMSPt and DMSOt. In terms of biological factors, Prochlorococcus and Synechococcus were significant contributors to DMS (P, O) dynamics. Synechococcus was the dominant influence on the DMS source and DMSPt sink, whereas Prochlorococcus primarily consumed DMSOt. Furthermore, the structural equation modeling (SEM) revealed the relationship between DMS, DMSPt, DMSOt, and the key environmental/biological factors, as well as among them, and together they formed a co-regulatory network in the EIO. This contributes significantly to the advancement of global ecosystem models for DMS (P, O).

Effects of exercise-targeted hippocampal PDE-4 methylation on synaptic plasticity and spatial learning/memory impairments in D-galactose-induced aging rats - Yu Jin; Xue Li; Changling Wei; Qiongjia Yuan (Experimental Brain Research, 2024)
Physical exercise reduces the effects of aging and cognitive decline by improving synaptic plasticity and spatial learning. However, the underlying neurobiological mechanisms are unclear. A total of 45 Male SPF Sprague–Dawley rats were acclimatized and then allocated into three groups, 15 in each group: the saline control (DC) group, D-gal-induced aging (DA) group, and D-gal-induced aging + exercise (DE) group. Six weeks of intraperitoneal injections of D-gal at a concentration of 100 mg/kg body weight/d was injected to establish model of aging in the DA and DE groups. Morris water maze test was implemented to evaluate the hippocampus related cognition. SOD activity and MDA was tested to assess the aging in all groups. H&E and Nissl staining was used to observe the histopathological changes of hippocampal neurons in aging rats. Quantitative real-time polymerase chain reaction, western blotting and immunofluorescence staining techniques were used to investigate the expression of synaptic genes and proteins in the hippocampus. Massarray methylation system was employed to measure the PDE-4 gene methylation level in rat hippocampal tissues. Our results demonstrated that exercise intervention improves cognitive function in D-gal-induced aging rats. The methylation of CpG sites in PDE-4 in the hippocampus was significantly increased. The physical exercise significantly increased PDE-4 gene methylation and effectively decreased PDE-4 gene and protein expression. These beneficial behavioral and morphological effects were attributed to PDE-4 methylation, which was activated cAMP/PKA/CREB pathway and improved synaptic plasticity. Exercise induced PDE-4 methylation is key mechanism underpinning the amelioration of learning/memory impairment, suggesting the potential efficacy of physical exercise training in delaying brain aging.

Implications for practical application of commercial reduced iron powders to activate aqueous sulfite for decontamination of organics - Xiaoyi Lou; Changling Fang; Yaoguang Guo; Tianyi Zhou; Jie Guan; Huijuan Yu; Xuefeng Zhu (Arabian Journal of Geosciences, 2021)

Baseline sensitivity of natural population and resistance risk of Peronophythora litchii to four novel QoI fungicides - Yuxin Zhou; Lei Chen; Jian Hu; Pengfei Liu; Yu Zhang; Qingxiao Meng; Bin Li; Naiguo Si; Changling Liu; Xili Liu (European Journal of Plant Pathology, 2016)